2021
DOI: 10.3855/jidc.13686
|View full text |Cite
|
Sign up to set email alerts
|

Lung Fibrosis Sequelae After Recovery from COVID-19 Infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that causes coronavirus diseases 2019 (COVID-19). The SARS-CoV-2 is very contagious and nobody is known to be immune to it. The post-infected lung would leave a scar known as fibrosis, a scar tissue. A study from Wuhan, China suggested the development of fibrosis, though it was too early to label these lung changes as irreversible fibrosis in a time range of 3 weeks. The occurrence of fibrosis indicates a chronic infection whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These can contribute to persistent lung damage, including the recovery period after discharge, and may eventually lead to PF ( John et al., 2021 ). The pathogenesis of PF in COVID-19 have been discussed in several studies ( John et al., 2021 ; Susanto et al., 2021 ; Xiang et al., 2022 ) and alveolar epithelial cell injury during lung infection with SARS-CoV-2 are reported to be the major cause for the occurrence of PF since they lead to infiltration of fibroblasts and inflammatory cells, resulting in the release of pro-fibrotic factors ( Martinez et al., 2017 ). Meanwhile, 83% of type II alveolar cells express angiotensin-converting enzyme 2 (ACE2), which is the primary receptor for SARS-CoV-2 and may partly explain alveolar epithelial cell injury ( Umemura et al., 2021 ; Bui et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These can contribute to persistent lung damage, including the recovery period after discharge, and may eventually lead to PF ( John et al., 2021 ). The pathogenesis of PF in COVID-19 have been discussed in several studies ( John et al., 2021 ; Susanto et al., 2021 ; Xiang et al., 2022 ) and alveolar epithelial cell injury during lung infection with SARS-CoV-2 are reported to be the major cause for the occurrence of PF since they lead to infiltration of fibroblasts and inflammatory cells, resulting in the release of pro-fibrotic factors ( Martinez et al., 2017 ). Meanwhile, 83% of type II alveolar cells express angiotensin-converting enzyme 2 (ACE2), which is the primary receptor for SARS-CoV-2 and may partly explain alveolar epithelial cell injury ( Umemura et al., 2021 ; Bui et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a CT thorax scan post resolution of symptoms demonstrated that the acute lung damage initially observed had fully resolved. The long-term effects of COVID-19 on pulmonary function remain relatively unexplored (15). By the completion of 1-year follow-up, no chronic fibrosis was detected on imaging in this kidney transplant recipient.…”
Section: Discussionmentioning
confidence: 89%
“…Though it gives rise to various types of symptoms such as fatigue, myalgia, psychological issue, and rare neurological and cardiologic complications, dyspnea is one of the commonest symptoms [6][7][8][9]. Patients suffering from COVID pneumonia also show lung fibrosis later, even after recovery from COVID-19 [16,17]. It can lead to altered lung functions, dyspnea, and reduced exercise and work capacity.…”
Section: Discussionmentioning
confidence: 99%